REVITALIZATION OF INDONESIAN ULEMA COUNCIL FATWA ABOUT INTELLECTUAL PROPERTY PROTECTION - Nugraha Pranadita (International Journal of Law Reconstruction, 2020)
In the current era of global globalization, there is not a single country in the world that can live alone. One issue that can disrupt relations between nations in the world is related to the protection of Intellectual Property Rights (IPR). This is due to the economic value of the use of IPR that can increase the country's competitiveness in international relations. Increasing IPR protection is a necessity to increase the creativity and productivity of the community, while at the same time increasing the trust of the international community which is ultimately expected to encourage the development of the national economy. One effort to improve IPR protection in Indonesia is to revitalize the fatwa of the Indonesian Ulema Council on IPR protection so that it can keep abreast of the times and can provide a deterrent effect to perpetrators of criminal acts of IPR violations, especially those who are Muslim. That is because his actions are contrary to Islamic law, so it is appropriate and should be sentenced both in the world and in the hereafter. The purpose of the preparation of this manuscript is to encourage changes to the MUI fatwa on IPR protection. This research is a normative legal research using the statutory and conceptual approach. The results of this study are the draft changes to the substance of the MUI fatwa on IPR Protection.